2015
DOI: 10.1017/s0142716415000521
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between bilingual effects and language impairment: Exploring grammatical markers in Spanish-speaking bilingual children

Abstract: This study examines the interaction between language impairment and different levels of bilingual proficiency. Specifically, we explore the potential of articles and direct object pronouns as clinical markers of primary language impairment (PLI) in bilingual Spanish-speaking children. The study compared children with PLI and typically developing children (TD) matched on age, English language proficiency, and mother’s education level. Two types of bilinguals were targeted: Spanish-dominant children with interme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 48 publications
4
32
1
1
Order By: Relevance
“…Bilinguals in her study acquired German determiners faster than German monolinguals, but the advantage was only detected for children with strong Italian abilities. In contrast, Castilla-Earls et al’s (2016) study with Spanish–English bilinguals showed delays for articles in Spanish. Children's level of English proficiency predicted the accurate production of articles in Spanish.…”
Section: Introductionmentioning
confidence: 77%
“…Bilinguals in her study acquired German determiners faster than German monolinguals, but the advantage was only detected for children with strong Italian abilities. In contrast, Castilla-Earls et al’s (2016) study with Spanish–English bilinguals showed delays for articles in Spanish. Children's level of English proficiency predicted the accurate production of articles in Spanish.…”
Section: Introductionmentioning
confidence: 77%
“…As noted, Prevoo et al (2015) have provided empirical support for a contextdependent view of interdependence. However, as language acquisition is driven by experience and is mediated by maturation and individual differences in learning abilities (Castilla-Earls et al, 2016), interdependence may not only depend on contextual factors. Internal factors may influence variation of the cross-linguistic relationship, too.…”
Section: Potential Factorsmentioning
confidence: 99%
“…The age at which the child starts learning L2 determines the course of bilingual development (Castilla-Earls et al, 2016). Bilingual children entering preschool at a later date have experienced less prior exposure to L2 than their counterparts who entered preschool at starting age.…”
Section: Onset Of Schooling In L2mentioning
confidence: 99%
“…The development of grammar in bilingual children with SLI was investigated in Castilla-Earls et al (2016), who addressed the production of articles and object pronouns in Spanishspeaking bilingual children. The study used an elicited production task and separated the children between balanced and Spanish-dominant bilinguals.…”
Section: Bilingualism and Sli: 2017mentioning
confidence: 99%